2017
DOI: 10.3310/hta21240
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and cost-effectiveness of a multifaceted podiatry intervention for falls prevention in older people: a multicentre cohort randomised controlled trial (the REducing Falls with ORthoses and a Multifaceted podiatry intervention trial)

Abstract: BackgroundFalls are a serious cause of morbidity and cost to individuals and society. Evidence suggests that foot problems and inappropriate footwear may increase the risk of falling. Podiatric interventions could help reduce falls; however, there is limited evidence regarding their clinical effectiveness and cost-effectiveness.ObjectivesTo determine the clinical effectiveness and cost-effectiveness of a multifaceted podiatry intervention for preventing falls in community-dwelling older people at risk of falli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 61 publications
0
39
0
2
Order By: Relevance
“…In the United Kingdom, a study on the use of a booklet for preventing falls in the elderly in the community also demonstrated good patient acceptability and practical applicability of the material. (25) Furthermore, it is important that studies involving new educational technologies assess their applicability in the context in which they will be used. (26) It is worth noting that the educational manual was not designed to replace the verbal guidance provided by the nurse during nursing care, but rather to reinforce the guidelines and solve doubts, since the patient can consult the material whenever they are interested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United Kingdom, a study on the use of a booklet for preventing falls in the elderly in the community also demonstrated good patient acceptability and practical applicability of the material. (25) Furthermore, it is important that studies involving new educational technologies assess their applicability in the context in which they will be used. (26) It is worth noting that the educational manual was not designed to replace the verbal guidance provided by the nurse during nursing care, but rather to reinforce the guidelines and solve doubts, since the patient can consult the material whenever they are interested.…”
Section: Discussionmentioning
confidence: 99%
“…(26) It is worth noting that the educational manual was not designed to replace the verbal guidance provided by the nurse during nursing care, but rather to reinforce the guidelines and solve doubts, since the patient can consult the material whenever they are interested. (25) It is suggested that nurses use the booklet during educational strategies and that, at that moment, this technology facilitates the construction of knowledge between nurse-patient-family, besides favoring clarification of doubts.…”
Section: Discussionmentioning
confidence: 99%
“…This trial was embedded within the National Institute for Health Research Health Technology Assessment (NIHR HTA) programme funded REFORM (REducing Falls with ORthoses and a Multifaceted podiatry intervention) study (registration number ISRCTN68240461; registration date, 1 st July 2011; http://www.isrctn.com/ISRCTN68240461) 10 , which aimed to evaluate the clinical and cost effectiveness of a podiatry intervention for the prevention of falls in older people. Ethical approval for the REFORM study and this embedded sub-study was given by National Research Ethics Service East of England – Cambridge East Research Ethics Committee (REC reference 11/EE/0379) and the University of York, Department of Health Sciences Research Governance Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Further details of the REFORM trial are provided in table 2 and the study has been published elsewhere. (10,11) In this paper we present findings of a qualitative process evaluation, which was conducted alongside the REFORM trial. Through interviews with podiatrists who delivered the REFORM intervention and trial participants we aim to explore some of the factors which affected the fidelity of the REFORM intervention.…”
Section: Insert Table 1 Herementioning
confidence: 99%